SARS-CoV-2 structure and replication characterized by in situ cryo-electron tomography - Klein, Steffen; Cortese, Mirko; Winter, Sophie L.; Wachsmuth-Melm, Moritz; Neufeldt, Christopher; Cerikan, Berati; Stanifer, Megan; Boulant, Steeve; Bartenschlager, Ralf; Chlanda, Petr (Nature Communications, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of the COVID19 pandemic, is a highly pathogenic β-coronavirus. As other coronaviruses, SARS-CoV-2 is enveloped, replicates in the cytoplasm and assembles at intracellular membranes. Here, we structurally characterize the viral replication compartment and report critical insights into the budding mechanism of the virus, and the structure of extracellular virions close to their native state by in situ cryo-electron tomography and subtomogram averaging. We directly visualize RNA filaments inside the double membrane vesicles, compartments associated with viral replication. The RNA filaments show a diameter consistent with double-stranded RNA and frequent branching likely representing RNA secondary structures. We report that assembled S trimers in lumenal cisternae do not alone induce membrane bending but laterally reorganize on the envelope during virion assembly. The viral ribonucleoprotein complexes (vRNPs) are accumulated at the curved membrane characteristic for budding sites suggesting that vRNP recruitment is enhanced by membrane curvature. Subtomogram averaging shows that vRNPs are distinct cylindrical assemblies. We propose that the genome is packaged around multiple separate vRNP complexes, thereby allowing incorporation of the unusually large coronavirus genome into the virion while maintaining high steric flexibility between the vRNPs.